Dinâmica dos resíduos vegetais em latossolo sob diferentes sistemas de uso - Carvalho, Mary Anne Barbosa de (2019)
The replacement of organic matter in the soil is a great option to improve soil quality. Therefore, the use of agricultural crops, such as straw, among others, can contribute to the sustainability and sustainability of various production systems, amortizing operating expenses and increasing income, making agriculture more sustainable. A dynamics of the decomposition and quantification of a mineralization rate of the Corn plant (Zea mays L.) on a Latossolo Amarelo distrófico (Ferralsol) under the no-tillage system under the conditions of the Brejo Paraibano microregion was determined. The experiments of fertilization and decomposition kinetics were conducted in the years 2013 to 2017, in the experimental area of Chã-de-Jardim, belonging to the CCA, UFPB, Areia-PB municipality. The fertilization experiment was set up for a randomized complete block design, with 11 treatments and 5 replicates, which were consummated using an exponential matrix Puebla III Plan, where N (0, 5, 30, 50, 70 and 95 kg ha-1) as urea, and for K (0, 4; 24; 40; 56 and 76 kg ha-1) as KCl. The dynamics of decomposition of the cultural residues of corn (stem, leaf, straw) for 150 days. At 30 days, organic carbon, total nitrogen, cellulose, hemicellulose and lignin were separated, the liquid residues in the pockets. Soil sampling was always performed after a harvest of each year. Samples of five portions per plot were collected to make a composition in the 0 to 20 cm depth layer. After passage from dry to air (TFSA) as passages were passed in sieve (2 mm). The soil pH and the contents of P, K+, Ca2+, Mg2+, H+ + Al3+ e CO. Were studied in different systems of use (FOREST, CONTROL, CORN, POUSIO). Three simple units were collected forming a composite, with five replicates, in the depths of 0 - 10 and 10 - 20 cm, in deep depths, a collection of undisturbed samples was carried out to determine the soil density (Ds). The snail was totally absorbed to the depth of 0 to 10 cm. For both the analysis of variance and the estimation of the parameters of the exponential equation, the statistical package SAEG version 9.1 was used. Nitrogen fertilization is not influenced by the rate of decomposition of the corn residue, nor in its routine constituents. The nutrient contents released during the decomposition of maize biomass in a period of 5 years are generally not differentiated between treatments with fertilization and without mineral fertilization. Compared to the CONTR, nitrogen and potassium fertilization did not alter soil C levels at depths of 0 - 10 and 10 - 20 cm.